Small and Vulnerable : Small Firm Productivity in the Great Productivity Slowdown - Chen, Sophia (IMF Working Papers; Working Paper ;, 2020)
We provide broad-based evidence of a firm size premium of total factor productivity (TFP) growth in Europe after the Global Financial Crisis. The TFP growth of smaller firms was more adversely affected and diverged from their larger counterparts after the crisis. The impact was progressively larger for medium, small, and micro firms relative to large firms. It was also disproportionally larger for firms with limited credit market access. Moreover, smaller firms were less likely to have access to safer banks: those that were better capitalized banks and with a presence in the credit default swap market. Horseraces suggest that firm size may be a more important and robust vulnerability indicator than balance sheet characteristics. Our results imply that the tightening of credit market conditions during the crisis, coupled with limited credit market access especially among micro, small, and medium firms, may have contributed to the large and persistent drop in aggregate TFP.